Turbidity effects on the Aegean sea surface properties using numerical simulations - Metheniti, Vassiliki; Vervatis, Vassilios; Kampanis, Nikolaos; Sofianos, Sarantis (2024)
This study examines the impact of different turbidity products on the Aegean Sea surface physical characteristics, by performing twin-experiment simulations using a high-resolution regional ocean model. The turbidity products used include an in-situ based diffuse attenuation coefficient dataset at 490 nm (kd490, in m− 1) and a satellite derived kd490 product. Satellite turbidity products are broadly used in ocean simulations due to their spatiotemporal coverage and algorithm universality. Their validation and empirical components are trained mainly in phytoplankton driven regions and this may cause systematic differences in oligotrophic areas of variable optical properties’ composition. In the Aegean Sea, the in-situ based turbidity product accounts for the contribution of suspended particles in the solar heating profile, having further implications in the surface characteristics. The Aegean Sea upper-ocean thermohaline characteristics and general circulation patterns, reveal distinct differences between the twin-experiment simulations, showcasing mesoscale to locally induced impact of the turbidity variations. The turbidity impact on the air-sea interaction fluxes affects both thermodynamic processes i.e., solar radiation penetration and absorption in the water column, as well as dynamic processes i.e., momentum fluxes due to changes of the sea surface temperature and subsequently to the momentum drag coefficient. The Aegean Sea surface characteristics in the in-situ based turbidity product simulation, show a stronger decoupling between the North and the South Aegean Sea, when compared with the satellite derived turbidity product simulation. These results highlight the importance of incorporating more realistic turbidity products in ocean models, especially for optically complex regions such as the Aegean Sea.